Chondroprotective activity of N-acetyl phenylalanine glucosamine derivative on knee joint structure and inflammation in a murine model of osteoarthritis. Issue 4 (April 2017) - Veronesi, F.; Giavaresi, G.; Maglio, M.; Scotto d'Abusco, A.; Politi, L.; Scandurra, R.; Olivotto, E.; Grigolo, B.; Borzì, R.M.; Fini, M.
Summary: Objective: Osteoarthritis (OA), the most common chronic degenerative joint disease, is characterized by joint structure changes and inflammation, both mediated by the IκB kinase (IKK) signalosome complex. The ability of N-acetyl phenylalanine derivative (NAPA) to increase cartilage matrix components and to reduce inflammatory cytokines, inhibiting IKKα kinase activity, has been observed in vitro . The present study aims to further clarify the effect of NAPA in counteracting OA progression, in an in vivo mouse model after destabilization of the medial meniscus (DMM). Design: 26 mice were divided into three groups: (1) DMM surgery without treatment; (2) DMM surgery treated after 2 weeks with one intra-articular injection of NAPA (2.5 mM) and (3) no DMM surgery. At the end of experimental times, both knee joints of the animals were analyzed through histology, histomorphometry, immunohistochemistry and microhardness of subchondral bone (SB) tests. Results: The injection of NAPA significantly improved cartilage thickness (CT) and reduced Chambers and Mankin modified scores and fibrillation index (FI), with weaker MMP13, ADAMTS5, MMP10 and IKKα staining. The microhardness measurements did not shown statistically significant differences between the different groups. Conclusions: NAPA markedly improved the physical structure of articular cartilage while reducing catabolic enzymes, extracellular matrix (ECM) remodeling and IKKα expression, showing to be able to exert a chondroprotective activity in vivo .